Ablation of mouse adult neurogenesis alters olfactory bulb structure and olfactory fear conditioning - Valley, Matthew; Mullen, Tanner R.; Schultz, Lucy; Sagdullaev, Botir T.; Firestein, Stuart (Frontiers in Neuroscience, 2009)
Adult neurogenesis replenishes olfactory bulb (OB) interneurons throughout the life of most mammals, yet during this constant fl ux it remains unclear how the OB maintains a constant structure and function. In the mouse OB, we investigated the dynamics of turnover and its impact on olfactory function by ablating adult neurogenesis with an x-ray lesion to the subventricular zone (SVZ). Regardless of the magnitude of the lesion to the SVZ, we found no change in the survival of young adult born granule cells (GCs) born after the lesion, and a gradual decrease in the population of GCs born before the lesion. After a lesion producing a 96% reduction of incoming adult born GCs to the OB, we found a diminished behavioral fear response to conditioned odor cues but not to audio cues. Interestingly, despite this behavioral defi cit and gradual anatomical changes, we found no electrophysiological changes in the GC population assayed in vivo through dendro-dendritic synaptic plasticity and odor-evoked local fi eld potential oscillations. These data indicate that turnover in the granule cell layer is generally decoupled from the rate of adult neurogenesis, and that OB adult neurogenesis plays a role in a wide behavioral system extending beyond the OB.